2016
DOI: 10.1016/j.jpeds.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hemoglobin Concentration during Gestation and Risk of Anemia in Infancy: Secondary Analysis of a Randomized Controlled Trial

Abstract: Objective To examine the relationship between maternal hemoglobin (Hb) concentration and the risk of anemia in infancy. Study design This analysis included 17,193 women who entered the trial when they were 20 years of age or older, no more than 20 weeks of gestation, had mild or no anemia, and delivered singleton live births. Maternal Hb concentrations were measured in the first trimester and during 24-28 weeks of gestation; infant Hb concentrations were measured at 5-7 months and 11-13 months of life. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…It can be severe to the acute life-threatening event [7]. It also causes impairment in brain development, delay in brain maturation, poor school performance and work capacity in later years, stunted growth, tissue and organ hypoxia, poorer cognitive, motor, and social-emotional development [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…It can be severe to the acute life-threatening event [7]. It also causes impairment in brain development, delay in brain maturation, poor school performance and work capacity in later years, stunted growth, tissue and organ hypoxia, poorer cognitive, motor, and social-emotional development [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, a lot of physiologic changes occur to accommodate the demands of the developing fetus, which affects the hematologic parameters directly or indirectly. These hematologic changes are considered to be the risk factors affecting maternal and pregnancy outcome . For hematologic complication that can be discriminated and treated early, it is important to know the variation during the entire stages of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…These hematologic changes are considered to be the risk factors affecting maternal and pregnancy outcome. [5][6][7][8] For hematologic complication that can be discriminated and treated early, it is important to know the variation during the entire stages of pregnancy. Thus, to understand the changes better and distinguish whether it caused by physiologic or pathologic, there is a basic need *These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia due to chronic diseases is one of the proposed mechanisms of schistosomiasis-mediated adverse birth and neonatal outcomes [12]. In particular, schistosomiasis in pregnancy is responsible for iron loss in stool and urine, resulting in maternal iron deficiency and anemia, which has been associated with infant's hemoglobin concentration in the first months of life [30][31][32]. However, in our study the effect of schistosomiasis on infant's Hb concentration was shown after adjustment for maternal anemia, suggesting other underlying mechanisms.…”
Section: Risk Of Febrile Infectionmentioning
confidence: 99%